Rehabilitation of degraded forests to improve livelihoods of poor farmers in South China - Liu Dachang (Center for International Forestry Research, 2003)
Degradation of forests and forest lands is a problem in many parts of the world and is particularly serious in south China. Chinese forest policy reforms in recent years have enabled rural households to generate income from forests, to own the trees they have planted, and have offered new opportunities to manage forests sustainably. Rehabilitation of degraded forests and forest lands is one of the possible pathways to improve livelihoods of poor farmers and others in the rural communities. This report documents the results of four case studies in south China in which farmers, local officials and ressearchers anlysed the problems of degraded forests and forest lands, and formulated options for their solution. Opportunities to improve forest management and people's livelihoods are dependent on overcoming a range of biophysical, socioeconomic and political constraints. Action research was used to implement and test some of the options identified. The experience and analysis should be of value for researchers, resource managers and government officials in China and elsewhere to address poverty and environmental concerns through a multidisciplinary, participatory and holistic approach.